2003
DOI: 10.1186/1471-2156-4-s1-s101
|View full text |Cite
|
Sign up to set email alerts
|

Genomic regions linked to alcohol consumption in the Framingham Heart Study

Abstract: Background: Pedigree, demographic, square-root transformed maximum alcohol (SRMAXAPD) and maximum cigarette (MAXCPD) consumption, and genome-wide scan data from the Framingham Heart Study (FHS) were used to investigate genetic factors that may affect alcohol and cigarette consumption in this population-based sample.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
64
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(68 citation statements)
references
References 23 publications
4
64
0
Order By: Relevance
“…Of these 10 significant or highly significant linkages for smoking quantity, eight of them located on chromosomes 1, 4, 7, 8, 11, 16, 17, and 20 were also reported by one or more research groups [22][23][24][25] previously with the FHS smoking data at a nominal significance level, with a P-value of around 0.05 or LOD score between 1.0 and 2.0, except for the results reported by our group 25 in which we found significant evidence for linkage on chromosome 11 (pointwise Pvalue ¼ 10 À6 ) and suggestive evidence on chromosomes 4, 7, and 17 with a pointwise P-value of less than 0.0017. Nevertheless, our study does not represent a simple replication of those early works.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Of these 10 significant or highly significant linkages for smoking quantity, eight of them located on chromosomes 1, 4, 7, 8, 11, 16, 17, and 20 were also reported by one or more research groups [22][23][24][25] previously with the FHS smoking data at a nominal significance level, with a P-value of around 0.05 or LOD score between 1.0 and 2.0, except for the results reported by our group 25 in which we found significant evidence for linkage on chromosome 11 (pointwise Pvalue ¼ 10 À6 ) and suggestive evidence on chromosomes 4, 7, and 17 with a pointwise P-value of less than 0.0017. Nevertheless, our study does not represent a simple replication of those early works.…”
Section: Discussionmentioning
confidence: 93%
“…3 Recently, several research groups have performed linkage analyses with the smoking data of the FHS that were made available through the Genetic Analysis Workshop (GAW) 13. [22][23][24][25] In aggregate, these studies reported approximately 29 potential linkage regions for the smoking behavior. These potential linkage regions were located on most of the 22 autosomal chromosomes except chromosomes 3, 10, 18, and 19 (no genotypic data were available on the sex chromosomes).…”
Section: Introductionmentioning
confidence: 99%
“…Although the prevalence of smoking has decreased significantly in many countries, particularly among men, the number of highly dependent smokers has not declined correspondingly. 28 In previous linkage analyses, smoking behavior as a phenotype has been defined in several different ways: average 7,15 or maximum 29,30 number of cigarettes smoked per day, ever smoking, 31 habitual smoking 17,18 and total number of cigarette packs per day for 1 year. 14 Similarly, ND can be defined in various ways, the most commonly used definitions being based on the DSM-IV 32 and the FTND.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24][25][26][27][28][29][30][31][32][33][34] Only a few of the results of these studies have converged convincingly, with the major linkage peak produced by a number of studies being poorly, if at all, supported by subsequent data (e.g., see [22][23][24][25][26] ). Indeed, assemblies of current results from at least some linkage-based genomes can produce results that cover the majority of the genome with data that derive from at least some reported linkage peak in at least one study (C Johnson, GR Uhl, unpublished observations, 2005).…”
Section: The Scope Of Current Molecular Genetic Data For Addictionsmentioning
confidence: 99%